2013
DOI: 10.1055/s-0033-1356169
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Guided and CT-Guided Cervical Nerve Root Infiltration Therapy: A Cost Comparison

Abstract: Purpose: To evaluate and compare the costs of MRI-guided and CT-guided cervical nerve root infiltration for the minimally invasive treatment of radicular neck pain. Materials and Methods: Between September 2009 and April 2012, 22 patients (9 men, 13 women; mean age: 48.2 years) underwent MRI-guided (1.0 Tesla, Panorama HFO, Philips) single-site periradicular cervical nerve root infiltration with 40?mg triamcinolone acetonide. A further 64 patients (34 men, 30 women; mean age: 50.3 years) were treated under CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Rempp et al [24] reported average procedure durations from planning imaging to control imaging of 3.7 h for MR-guided RF ablation in hepatic malignancies with a mean tumour diameter of 20 mm. These procedure durations are a major drawback of MR-guided interventions given the limited availability of MR scanners and higher costs of this modality in comparison to CT and ultrasound [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Rempp et al [24] reported average procedure durations from planning imaging to control imaging of 3.7 h for MR-guided RF ablation in hepatic malignancies with a mean tumour diameter of 20 mm. These procedure durations are a major drawback of MR-guided interventions given the limited availability of MR scanners and higher costs of this modality in comparison to CT and ultrasound [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Using MRI as a guidance modality in percutaneous ablation procedures is currently limited to a few centres specialised in MR-guided interventions, even though MR-guidance offers several advantages such as near real-time fluoroscopic sequences [11], free selection of imaging planes [12], higher sensitivity in depicting small parenchymal lesions [13], assessment of the ablation zone without application of contrast agent and absence of ionising radiation [14]. The high operating costs of dedicated MRI-scanners combined with longer durations of MR-guided interventions prevent the increased use of MRguidance in interventional oncology [20]. However, the combination of microwave ablation and MR-guidance might be beneficial, as microwave ablation creates larger ablation zones in shorter time and with less applicator insertions than RF ablation [6,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…CT guidance is approximately 0.9 relative value units higher than fluoroscopy (3.32 for CT scan for therapy guide, versus 2.41 for fluoroscopic guidance for spine injection). In European cost-analysis studies, CT was demonstrated to be cheaper than magnetic resonance (MR) guidance for lumbosacral nerve root injection (28), and in between the cost of ultrasound and MR guidance for cervical nerve root injection (29). As cost and resources vary by health care facility and geographic location, the scale and potential impact of these differences should be considered in the individualized setting.…”
Section: Discussionmentioning
confidence: 99%